Chris Cunningham: autoria em videoclipe - Andrade, Sueli Chaves (2009)
The work from the video artist Chris Cunningham is the main theme of this research. The several audiovisual productions of this director include video installations, advertising and mainly music videos. There are two reasons for the choice of this object. The first one is related to the contemporary themes of Cunningham´s projects such as cyborg and freak bodies in the context of the post-human issue. The second reason is the possibility of placing the British as author in the audiovisual field. The music videos All Is Full Of Love (1999) and Rubber Johnny (2005) are the selected works for analysis of this research. The theoretical references over which this investigation is supported are related to the issues of authorship, post-cinema images and post-human body. Around the authorship discussion this research can be placed on debates proposed by the traditional French journal Cahiers du Cinéma during 1950s and the machine-artist relationship proposed by Vilém Flusser in Towards a Philosophy of Photography. To discuss the music video the selected authors are Arlindo Machado, E. Ann Kaplan and the pop culture experts Andrew Goodwin and Simon Fritch. Besides there are also the theorists Raymond Bellour (1997) who provides a place to the video and Philippe Dubois (2004) who suggests to think of it as a state and not as a product since it´s intimately tied to the device for which it has been designed. The approach to the body theme is based on works from Lucia Santaella, Paula Sibilia and Ieda Tucherman